2012
DOI: 10.1371/journal.pone.0029591
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Survival and Economic Benefits of Deceased Donor Kidney Transplantation and Dialysis in People with Varying Ages and Co-Morbidities

Abstract: BackgroundDeceased donor kidneys for transplantation are in most countries allocated preferentially to recipients who have limited co-morbidities. Little is known about the incremental health and economic gain from transplanting those with co-morbidities compared to remaining on dialysis. The aim of our study is to estimate the average and incremental survival benefits and health care costs of listing and transplantation compared to dialysis among individuals with varying co-morbidities.MethodsA probabilistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
114
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(117 citation statements)
references
References 37 publications
0
114
0
2
Order By: Relevance
“…Kidney transplantation significantly improves life expectancy and reduces costs for dialysis patients (2,15), but this improvement has not been shown in predialysis CKD. Although time on dialysis (dialysis vintage) strongly associates with recipient mortality (16)(17)(18), no study has shown that preemptive DDKT improves on DDKT among those patients with short dialysis vintage.…”
Section: Introductionmentioning
confidence: 99%
“…Kidney transplantation significantly improves life expectancy and reduces costs for dialysis patients (2,15), but this improvement has not been shown in predialysis CKD. Although time on dialysis (dialysis vintage) strongly associates with recipient mortality (16)(17)(18), no study has shown that preemptive DDKT improves on DDKT among those patients with short dialysis vintage.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Organs routinely transplanted include heart, lung, liver, pancreas, and bowel but other organs that may be transplanted include thymus, hand, face, leg, abdominal wall, and uterus. The last two decades have seen major changes in organ transplantation: developments in surgery, anaesthesia, interventional radiology, microbiology, and pharmacology have transformed what many still today believe is a high intensity, high risk procedure with a high mortality to a routine procedure with low morbidity and a high long-term success rate.…”
mentioning
confidence: 99%
“…Over a fiveyear period, a kidney transplant saves the health care system over $100,000 compared with in-clinic dialysis (ibid). A number of studies have found transplants to be more cost effective than dialysis (Wong et al, 2012;Howard et al, 2009). From political and economic perspectives, increasing the number of transplants performed is highly desirable.…”
Section: Why Should We Be Concerned About the Organ Scarcity Discourse?mentioning
confidence: 99%